Childhood family and neighbourhood socio-economic status, psychopathy, and adult criminal behaviour - Baker, Sydney (Legal and criminological psychology, 2023)
Purpose Lower socio-economic status (SES) and psychopathy are risk factors for criminal behaviour. This study examines whether psychopathic trait scores moderate the relationship between childhood family and neighbourhood SES and adult arrests. Methods A large group of Midwest children ages 0–11 years old during 1967–1971 were interviewed as adults in 1989–1995 (N = 1144) at mean age 29. Childhood family SES was based on information collected during the interview and neighbourhood SES were based on census tract information from childhood. Psychopathic trait scores were based on information from interviews and case records. Official arrest data were used to assess criminal behaviour in adulthood. Results Childhood family SES, childhood neighbourhood SES, and psychopathic trait scores each independently predicted the number of adult arrests. As expected, lower childhood family SES and childhood neighbourhood SES predicted a larger number of adult arrests, and higher psychopathic trait scores were associated with a greater number of adult arrests. Childhood family SES and childhood neighbourhood SES also interacted with psychopathic trait scores to predict adult arrests. For individuals with low psychopathic trait scores, lower childhood family SES and lower childhood neighbourhood SES each predicted a higher number of adult arrests, whereas this was not the case for individuals with high psychopathic trait scores. Conclusions Childhood SES (family and neighbourhood) continues to affect criminal behaviour long into adulthood. But neither childhood family SES, childhood neighbourhood SES, or psychopathic traits alone explain the extent of adult arrests. For people with comparably low levels of psychopathic traits, childhood family and neighbourhood socio-economic status continued to impact adult arrests.